2021
DOI: 10.30880/jtet.2021.13.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study for Technical and Vocational Education and Training Professional Development Training in Untact Era: Focusing on Official Development Assistance Project in Botswana

Abstract: The prolonged COVID-19 pandemic has disrupted the TVET professional development training, which was planned to be carried out in a face-to-face manner. This study aims to examine TVET professional development training based on the ADDIE model and provide implications for ODA and TVET professional development training in the post-COVID era. In this case study, a TVET training program for Botswana was developed based on the ADDIE model in an untact environment. Accordingly, the performance activities for each ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The underlying premise of e-learning and mobile technologies has long been its quality of accessibility and value at reduced costs (Crompton, 2013; Bukharaev and Altaher, 2017; Ra et al , 2019). Our findings revealed that mobile accessibility (Lim and Yi, 2021), online adaptation of training (Lee et al , 2021) and availability to remote geographical areas (Arisanti et al , 2019) provided strong affordances in using e-learning and mobile platform technologies. Researchers (namely, Choudhury and Pattnaik, 2020) have suggested that shareholders of organizations have recognized e-learning as consistently providing large-scale dissemination of knowledge, reducing travel and improving business responsiveness across generations of technologies, resulting in its emergence as a strategic asset in organizational learning.…”
Section: Question 4 How Did the Use Of Technology Benefit The Develop...mentioning
confidence: 76%
See 1 more Smart Citation
“…The underlying premise of e-learning and mobile technologies has long been its quality of accessibility and value at reduced costs (Crompton, 2013; Bukharaev and Altaher, 2017; Ra et al , 2019). Our findings revealed that mobile accessibility (Lim and Yi, 2021), online adaptation of training (Lee et al , 2021) and availability to remote geographical areas (Arisanti et al , 2019) provided strong affordances in using e-learning and mobile platform technologies. Researchers (namely, Choudhury and Pattnaik, 2020) have suggested that shareholders of organizations have recognized e-learning as consistently providing large-scale dissemination of knowledge, reducing travel and improving business responsiveness across generations of technologies, resulting in its emergence as a strategic asset in organizational learning.…”
Section: Question 4 How Did the Use Of Technology Benefit The Develop...mentioning
confidence: 76%
“…However, a few simple technologies were noted in the analysis phase of the studies. For example, Lee et al (2021) used audiotape to record interviews with nurse professionals to analyze nurse practitioner training needs and transcribed the interviews to analyze data and extract themes. The analysis of this data aligns with the ADDIE model, where information gathering and data collection are paramount using research techniques such as needs analyses, task analyses and other research techniques to construct the foundation of the training solution (Dick et al , 2001).…”
Section: Discussionmentioning
confidence: 99%